Paraneoplastic vasculitis in patients with metastatic renal cell carcinoma. Issue 2 (16th October 2018) - Tsimafeyeu, Ilya; Leonenko, Valentina; Kuznetsov, Vladimir; Semenkova, Evgenia; Bondarenko, Anastasia; Demidov, Lev
Abstract: Background: A paraneoplastic syndrome is observed in 5% to 10% of cancer patients. Paraneoplastic vasculitis (PV) in metastatic renal cell carcinoma (mRCC) patients has been poorly investigated. Aims: In our case series study, we evaluated the incidence and development of PV in patients with mRCC. Methods and results: Patients were required to have previously untreated clear‐cell or papillary mRCC and no evidence of autoimmune diseases or venous thrombosis in history. Patients had a careful examination including Doppler ultrasonography of the blood vessels and skin punch biopsy in the presence of suspicious skin rash. Sixteen (8.2%) of 196 patients were diagnosed with PV, which was manifested clinically by leukocytoclastic vasculitis on the lower extremities. Skin biopsy confirmed vasculitis. Progression‐free survival and overall survival were significantly better in patients without PV. Conclusions: PV is not rare paraneoplastic syndrome in mRCC. Leukocytoclastic vasculitis was the most common type of PV in this study.